Սուրեն Այվազյանի «Ձորերի ձայնը» պատմվածաշարը - Նիկոյան, Էմմա
Suren Ayvazyan’s short stories have a wide range of spatial-temporal inclusions. His protagonists are people of the period of Collectivization, World War II, and Social reorganization of village with their concerns and anxieties, peculiarities of outlook. Thematic, genre and structural peculiarities of these short stories are revealed in the presented article. У рассказов Сурена Айвазяна широкий спектр пространственно- временных включений. Его герои – люди времен коллективизации, Великой Отечественной войны, социальных преобразований деревни со своими заботами и переживаниями, особенностями мировоззрения. В статье рассматриваются тематические, жанровые, структурные особенности этих рассказов.
Keywords: Գրականագիտություն